ROLE MODEL OF WEBSITE QUALITY AND CUSTOMER SERVICE ON CUSTOMER SATISFACTION - M. SHALAHUDDIN FADHLUL FIKRI (Lentera Barasaki Publishing House, 2023)
This study investigates the effect of website quality and customer service on customer satisfaction at PT Mbeawya Digital Solution. Website quality is measured through information, interactivity, and design, while the quality of customer service is measured through reliability, responsiveness, assurance, and empathy. The survey method was used with 100 respondents, and multiple linear regression analysis was performed. The results showed that website quality and customer service had a positive effect on customer satisfaction at PT Mbeawya Digital Solution. Aspects such as information, interactivity, and website design provide a positive experience. Companies need to improve the quality of websites with comprehensive information, better interactivity, and attractive designs. Customer service also needs to be improved with a focus on reliability, responsiveness, product quality assurance, and empathy for customer needs. Customer feedback and competitor analysis also help improve website quality and customer service.